Análisis de los factores de riesgo psicosocial y su incidencia en los programas de formación de trabajo en alturas, para su incorporación en los centros de entrenamiento en la ciudad de Barranquilla (2024)
The research proposes to analyze the presence of psychosocial risk factors, which negatively affect the effectiveness and safety of training programs for work at heights, and therefore, have a negative effect on the performance of the trainers who carry out this work. in the training centers of the city of Barranquilla; The absence of a methodology to review these psychosocial risks does not allow trainers to impart knowledge in an articulated manner. The research proposes a survey of work at height trainers, to know their perception regarding psychosocial risks, and the influence of these on the different levels of training at height. To argue the purpose of the research, the results of the survey of 80% of the work at height trainers who work in the different training centers of Barranquilla were considered. The result obtained showed a greater tendency towards medium-level psychosocial risk, interpreting this result as that the majority of the surveyed population is at a risk level in which a moderate stress response would be expected and that also the dimensions and domains Those that fall under this category merit observation and systematic intervention actions to prevent harmful effects on health. With these results, the design of a diagnostic instrument is proposed that allows the identification and evaluation of psychosocial risk factors, so that it can be applied to work at height trainers by training centers certified by the Ministry of Labor, in the city of Barranquilla